2011
DOI: 10.2478/v10173-011-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal properties of large bubble paths in a single bubble column

Abstract: In the paper the paths of bubbles emitted from the brass nozzle with inner diameter equal to 1.6 mm have been analyzed. The mean frequency of bubble departure was in the range from 2 to 65.1 Hz. Bubble paths have been recorded using a high speed camera. The image analysis technique has been used to obtain the bubble paths for different mean frequencies of bubble departures. The multifractal analysis (WTMM -wavelet transform modulus maxima methodology) has been used to investigate the properties of bubble paths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the papers [15,16] the paths of bubbles emitted from the brass nozzle have been analysed. It has been shown that bubble paths have multifractal character and its properties are changed when bubble departure frequency is greater than 30 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…In the papers [15,16] the paths of bubbles emitted from the brass nozzle have been analysed. It has been shown that bubble paths have multifractal character and its properties are changed when bubble departure frequency is greater than 30 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The MBR hydrodynamics are similar to bubble columns operation, with the difference that a membrane is placed inside the bubble column to extract the clean water. The placement of the membrane inside the column affects behaviour of the bubbles [2][3][4]. The main drawback of MBR systems is the fouling of the membrane, which results in frequent cleaning and replacement, making this system less appealing for full-scale applications [1].…”
Section: Introductionmentioning
confidence: 99%